PENGARUH PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PT. KORCHINA LOGISTICS INDONESIA JAKARTA - Yayuk Budi Iriyani Iriyani (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
The research objective to be achieved is to analyze the effect of promotions and service quality to customer satisfaction at PT. Korchina Logistics Indonesia Jakarta. The research method used is regression analysis, correlation, coefficient of determination and hypothesis testing both multiple and simple.The result of research is no effect either jointly or individually promotion and service quality to customer satisfaction at PT. Korchina Logistics Indonesia Jakarta. Conclusion; 1). No influence jointly variables sale and service quality to customer satisfaction can be seen from the F count = 9.544> F table at alpha = 0.05; DF = 2; 51. 2). There is an effect individually promotion variables to customer satisfaction can be seen from the results of the t = 29.220> t table = 1.684 at alpha = 0.05 DF = 2; 51. 3). No influence sendiril individually variable quality of service to customer satisfaction can be seen from the results of the t = 31.217> t table 1.684 at alpha = 0.05; DF = 2; 51.